Taletrectinib promotes pyroptosis in colorectal carcinoma via SRC/AKT/mTOR axis inhibition - Ting Zhang; Ye Zou; Sun-Han Zhang; Yuan-Yi Wang; Shuang He; Wei Yuan; Min Yang; Teng Liu; Shi-Hua Deng; Dong-Ming Wu; Ying Xu (Scientific Reports)
Abstract Drug resistance develops frequently after colorectal carcinoma (CRC) surgery, indicating the urgent need for new therapeutic strategies. Taletrectinib (DS-6051b/AB-106), a synthetic ROS1/NTRK inhibitor which has shown meaningful antitumor activity, is currently undergoing clinical trials aimed at addressing targeted resistance. However, the anti-cancer effect of taletrectinib on CRC remains unclear. In this study, our purpose was to evaluate taletrectinib-related cytotoxicity in vitro using two CRC cell lines, as well as in vivo in a mouse tumor model. The mechanism underlying the cytotoxicity of taletrectinib was evaluated using light microscopy, scanning electron microscopy, immunofluorescence assays, an annexin V-FITC/propidium iodide detection, lactate dehydrogenase (LDH) release assays, and western blotting. We found that the viability of CRC cells decreased with increasing concentrations of taletrectinib. In addition, transcriptome sequencing indicated that HCT116 and LOVO cell lines did not carry ROS1- or NTRK-related gene fusions and that the cytotoxic effect of taletrectinib was exerted via caspase-3/gasdermin E (GSDME)-dependent pyroptosis. Moreover, the effect of taletrectinib in promoting pyroptosis was reversed by treatment with the SRC agonist, tolimidone, both in vitro and in vivo. Overall, our findings suggest that taletrectinib suppresses tumor growth by inducing GSDME-mediated pyroptosis via the SRC/AKT/mTOR signaling pathway, indicating that taletrectinib shows potential as a promising therapeutic agent against CRC.